Benzodiazepines Withdrawal: Initial Outcomes and Long-Term Impact on Falls in a French Nursing Home - Hervé Javelot; Anne Marquis; Emilie Antoine-Bernard; Jean Grandidier; Luisa Weiner; Thierry Javelot; Bruno Michel (MDPI AG, 2018)
Long-term use of benzodiazepines (BZDs) is known to induce tolerance and dependence, and increase the risk of falls-related injuries in older adults. We present a study carried out in a French nursing home that concerns the implementation of a BZD withdrawal program reassessed at one year. BZD deprescription was achieved by gradual cessation of doses. A secondary benefit of this program was assessed by comparing the number of falls among residents before and after withdrawal. The number of falls was recorded over a six-month period prior to the onset of withdrawal (T1) and then over a six-month period after reassessment at one year (T2). At the beginning, 31 (28.7%) of the patients were under BZD. Total deprescription was obtained for 11 patients. The number of falls per patient over the T1 period was not different between the two groups (future non-withdrawn and withdrawn patients in BZD): 2.1 ± 1.3 and 2.3 ± 0.6 falls per resident, respectively. Conversely, the number of falls per patient was significantly decreased in the population completely withdrawn in BZD between the T1 and T2 periods (2.3 ± 0.6 vs. 0.5 ± 0.2 falls, p = 0.01). The results show that BZD deprescription, through a gradual reduction of doses, is possible to achieve.